Anticipatory Behaviour During the Approach to Feeding Times as a Measure of Horse Welfare - Fernando Mata; Georgina Boyton; Tamsin Young (Animals)
Anticipatory behaviour is increasingly being recognised as a measure of animal welfare. This behaviour is linked to reward sensitivity, which reflects the balance of positive and negative experiences. This study examined anticipatory behaviour in horses fed either ad libitum or rationed diets, aiming to identify differences in behaviour patterns during the periods of one hour immediately before and after feeding. Behavioural data were collected via video surveillance over five days, focusing on the pre- and post-feeding periods of stabled horses. The data were successfully fit to Poisson models. The results indicate that ration-fed horses exhibit more stereotypic and arousal behaviours, with anticipatory behaviour intensifying closer to feeding times. These findings suggest a potential link between feeding stress and anticipatory behaviour, especially in horses on rationed diets. This study underscores the importance of considering feeding practices in horse welfare management and highlights anticipatory behaviour as a valuable indicator for assessing animal well-being. Such assessments, rooted in circadian rhythms, offer a less resource-intensive means for ongoing welfare monitoring in animal care settings.